Multidrug efflux transporter, AcrB—the pumping mechanism - Murakami, Satoshi (Current opinion in structural biology, 2008)
Resistance nodulation cell division (RND) transporters are one of the main causes of the bacterial multidrug resistance. They pump a wide range of antibiotics out of the cell by proton motive force. AcrB is the major RND transporter in Escherichia coli. Recently, the crystal structures of AcrB have been determined by different space groups. All these structures are consistent with asymmetric trimer. Each monomer has different conformation corresponding to one of the three functional states of the transport cycle. Transporting hydrophobic drug was bound in the periplasmic domain on one of the three monomers. The transport pathway with alternating access mechanism is located at the hydrophilic domain protruded into the periplasmic space while this mechanism of other transporter families like ATP binding cassette (ABC) and major facilitator superfamily (MFS) transporter is located in the membrane-embedded region. For the RND, protonation might also take place asymmetrically at the functionally important charged residues in the transmembrane (TM) region. The structures indicate that drugs are transported by a three-step functional rotation in which substrates undergo ordered binding change.